Extraction and Characterization Gelatin of Skin Mackerel (Scomberomorus commersonii) From Province Bangka Belitung Island - Febri Gunawan; Pipih Suptijah; Uju Uju (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2017)
Mackerel (Scomberomorus commersonii) is one of the pelagic fish that has high economic value and iswidespread in Indonesia waters and potentially as a source of raw material of gelatin production derivedfrom skin. This study aimed to characterize the physico chemical properties of gelatin of mackerel withextraction with 3 time of replacement. Pretreatment with NaOH 0,1 M and 12 hours of immersion time,hydrolysis with CH3COOH 0,1 M for 3 hours, extracted with temperature 70˚C for 2 hours and evavorationwith temperature 60ºC for 60 minutes production gelatin of mackerel skin’s with physico chemicalcharacteristics of mackerel skin’s gelatin are known to have pH 5,47, gel strength 70,81 bloom, viscosity 5.51cP and color brightness L=70.78, a=1.44 and b=19.34. Yield 6.61±0.52%. The result of proximate analysisproduced protein (86.78±0.07%), water content (7.69±0.12%), lipid (0.71±0.07%) and ash (0.58±0.13%).The main amino acids were glysin (25.66%), prolin (12.73%), alanin (12.37%), asam glutamat (11.70%) andarginin (9.10%).